KEJADIAN PASIEN GAGAL JANTUNG DENGAN PENYAKIT KOMORBID HIPERTENSI DI RSUD ULIN BANJARMASIN - Reka Amelia; Dwi Laksono Adiputro; Agung Biworo; Mohammad Rudiansyah; Oski Illiandri (Homeostasis, 2022)
Heart failure is a clinical syndrome indicated by the lack of ability of the heart to supply enough blood to the peripheral tissues to fulfill the body's metabolic demands. In some cases, heart failure is usually accompanied by other pathological conditions where the process occurs at the same time as other diseases called comorbidities. In addition to the underlying disease, this disease is also a trigger, a risk factor, and a complication that further aggravates the condition of heart failure. Comorbidities are commonly found in elderly heart failure patients, resulting from the failure of several organ functions. However, the distribution of these comorbids varies in each age group. Uncontrolled hypertension causes complications of heart failure which is also a comorbid of heart failure itself. This study aims to determine the distribution of the incidence of heart failure patients with comorbid hypertension at Ulin Hospital Banjarmasin. This study used a retrospective descriptive research design with amethod total sampling by taking medical record data of heart failure patients who underwent outpatient treatment at Ulin Hospital Banjarmasin for the time range of February 2020-July 2020. From 188 heart failure patients during the time range of February 2020-July 2020, obtained as many as 84 (44.68%) patients with heart failure accompanied by hypertension. Based on the results of echocardiography, the most classifications were diastolic heart failure in 47 patients (55.95%), systolic heart failure in 21 patients (25%), and combination systolic diastolic heart failure in 16 patients (19.05%). The highest prevalence was in men 59 (70.24%). Conclusion: In patients with heart failure accompanied by comorbid hypertension, the most common finding is left ventricular diastolic heart failure, which predominantly affects male patients